2007
DOI: 10.1177/070674370705201103
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mechanisms of Episodic Memory Impairment in Schizophrenia

Abstract: These findings may explain some behavioural abnormalities associated with schizophrenia, notably, inadequate functional outcomes in everyday life. They may also have implications for cognitive remediation and better social and work functioning of patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 84 publications
6
74
1
13
Order By: Relevance
“…3,5,7,10 This was particularly true for episodic verbal memory, which is one of the most impaired memory domains in schizophrenia. 7,78 The effect sizes obtained for AM measures were in the same range, 3,5,7,10 suggesting that AM deficits must be regarded as a major domain of cognitive impairment in schizophrenia. This new finding has probably been under-acknowledged until today, despite that studies have shown that AM deficits are more reliable predictors of patients' reduced social performance than episodic memory (as assessed by traditional laboratory tasks) or clinical symptoms.…”
Section: Autobiographical Memory Deficits In Schizophreniamentioning
confidence: 79%
See 1 more Smart Citation
“…3,5,7,10 This was particularly true for episodic verbal memory, which is one of the most impaired memory domains in schizophrenia. 7,78 The effect sizes obtained for AM measures were in the same range, 3,5,7,10 suggesting that AM deficits must be regarded as a major domain of cognitive impairment in schizophrenia. This new finding has probably been under-acknowledged until today, despite that studies have shown that AM deficits are more reliable predictors of patients' reduced social performance than episodic memory (as assessed by traditional laboratory tasks) or clinical symptoms.…”
Section: Autobiographical Memory Deficits In Schizophreniamentioning
confidence: 79%
“…Research on episodic memory has provided evidence of defective strategic processes (due to executive dysfunction) during information encoding in patients with schizophrenia. 78,86 This may reflect patients' difficulty with spontaneously linking and organizing the different aspects of the material to be remembered. 87 These relational memory impairments described in schizophrenia 88,89 point to defective functioning of the hippocampus.…”
Section: Autobiographical Memory Deficits In Schizophreniamentioning
confidence: 99%
“…1,9,10 Within the domain of memory, recent studies have pointed to a specific deficit of relational memory in schizophrenia. [11][12][13][14][15][16] This provides the opportunity for more translational studies of cognitive impairment in schizophrenia because the neural circuitry and cellular mechanisms of relational memory have been elucidated in rodent and nonhuman primate studies. 17,18 Relational memory provides the ability to remember names with faces, the locations of various objects or people, and the order in which various events occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The precuneus is located in the posteromedial parietal cortex and plays an important role in a wide spectrum of highly-integrated tasks, including visuo-spatial imagery, episodic memory retrieval, and self-processing operations [55] . These cognitive functions are widely impaired in schizophrenia [56][57][58][59][60][61][62][63] . Moreover, the precuneus has been suggested to be the 'core node' of the default mode network [64] , which has been hypothesized to be relevant to the pathological mechanism of schizophrenia [65][66][67] .…”
Section: Discussionmentioning
confidence: 99%